Information grounds of business negotiations in international markets - Gregor, B.; Kalinska-Kula, М. (Видавництво Львівської політехніки, 2013)
The article presents an attempt to assess the degree and scope of using information obtained to support business negotiation processes conducted in international markets. The article includes the characterization of used information sources as well as an analysis of usefulness of obtained information in the context of satisfying information demand of negotiators. The study was based on the results of empirical research that was conducted on the sample of 267 enterprises using the method of direct interview. Наведено спробу оцінити ступінь і масштаби використання інформації, одержаної для підтримки процесів бізнес-переговорів, які проводяться на міжнародних ринках, а також характеристику використаних джерел інформації, а також аналіз корисності отриманої інформації в контексті задоволення інформаційного попиту переговірників. Дослідження ґрунтується на результатах емпіричних досліджень, які проводилися на 267 підприємствах, використовуючи метод прямого інтерв'ю.
Інформаційне підґрунтя проведення ділових переговорів на міжнародних ринках
Keywords: business negotiations; international negotiations; usefulness of information; sources of information; ділові переговори; міжнародні переговори; корисність інформації; джерела інформації